Pengaruh media pembelajaran berbasis aplikasi mobile terhadap keterampilan memahami teks berita peserta didik kelas V sekolah dasar di Kecamatan Laweyan - Priya Apriliana; Siti Istiyati; Septi Yulisetiani (Didaktika Dwija Indria, 2024)
The research aims to determine the effect of mobile application media on the news text comprehension skills of fifth grade elementary school students in Laweyan District, Surakarta. The research design is experimental, with a test data collection method. The data in this study were analysed using the paired sample t-test. The results of the paired sample t test on the hypothesis test which analysed the data from the post-test scores for the experimental class and control class were 0.018 < 0.05, which means the null hypothesis (H0) was rejected and the working hypothesis (H1) was accepted. Apart from that, there was a greater difference in the average post-test score compared to the pre-test in the experimental group, namely 76 > 64.5. Furthermore, the average post-test score for the experimental class is greater than the post-test score for the control class, namely 76 > 68.1. Based on the results of research analysis, it shows that mobile application media with news text material has an influence on the news text comprehension skills of fifth grade elementary school students in Laweyan District.